Who is behind the end of Spanish exclusivity? Analysis of the profile of the electorate of the “Vox” party - N. V. Kolpakov (Ибероамериканские тетради)
2 677 173 people voted for the “Vox” party in the April 2019 general election. Just seven months later, in November, that number increased to 3 640 063 votes, making “Vox” the third largest party in Spain in terms of both seats in the lower house of parliament (52 out of 350) and total votes (15.21%). “Vox” is a young Spanish right-wing party that was destined to remain small and insignificant, but ended up becoming one of the most influential actors in the country’s political space. Where other radical and far-right parties have failed, “Vox” has succeeded, and the party can now boast that it has put an end to Spain’s once exclusive status of a country free of right-wing politicians. The purpose of this article is to determine the electorate of this party, the success of which has become a real shock in the political arena of Spain. The author makes an analysis of socio-demographic profile of the “Vox” electorate. It is considered how class, education, age, gender and ideological views are associated with the support of “Vox.” “Vox” supporters differ significantly from supporters of both traditional and new Spanish parties. According to the analysis, “Vox” supporters are predominantly young males. The party has the smallest proportion of voters with higher education. “Vox” electorate is largely concentrated around those who strongly identify with Spain and the idea of “Hispanidad” and, above all, those who consider the country “under attack” from internal separatist forces (in Catalonia and the Basque country) and external cosmopolitanism, mainly in the form of immigration.